(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Purpose: Recent UNHCR figures show that a record 70.8 million refugees are forcibly displaced. Millions of refugees are trapped in protracted refugee situations, and have been so on average for 25 years; this compares with 17 years in 2003, and nine in 1991. The research addresses whether the existing international refugee law regime is capable of addressing this crisis, or whether the issue is that member states do not comply with the refugee regime Results: This research highlights the failure of European Union to respond to the refugee problems. The figures show that there are more refugees trapped in protracted situations than before and also that their plight takes longer to be resolved. Therefore, from the perspective of persons born in danger zones, one is more likely to be a refugee in 2019 than in 2014, yet less likely to find a durable solution. Methodology: The study adopted a doctrinal methodology by exploring legislation and directives to identify whether these laws can address refugee issues. Novelty/originality of this study: Forced migration has received negative media coverage and politicians, especially right-wing parties, have used migrants as a scapegoat. This paper identifies some of the myths of migration to demonstrate that, if given the opportunity, migrants can contribute positively to economic growth and integrate with local communities